Nilai dan Norma Sosial pada Masyarakat Nelayan untuk Memelihara Keberlanjutan Sumberdaya Ikan di Dataran Banjir Sungai Rungan, Palangka Raya - Bambang Sulistiyarto (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
This study aimed to reveal the social values and norms belonging fisher’s communities which play a role in maintaining the sustainability of fish resources in Rungan River floodplain, Palangka Raya. The study was conducted in the Petuk Ketimpun and Marang villages, in rural areas of Palangka Raya city, which is the principal place of fishing activities. Depth interviews were used to collect data and information. The results showed that the social values of fisher’s communities of Petuk Ketimpun and Marang generate wisely actions to maintain the sustainability of fish resources. Fisher’s communities have norms and social control to maintain the sustainability of fish resources. Strong social control occurred in territory controlled by the family of fisher’s, the main areas of fishing ground and the river in front of the settlement. Weak social control occurs in water areas far from the settlement.